2023
DOI: 10.31234/osf.io/gbk2j
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coping with Emotional Distress via Self-Disclosure to Robots: Intervention with Caregivers

Abstract: People often engage in various forms of self-disclosure and social sharing with others when trying to regulate the impact of emotional distress. Here we introduce a novel long-term mediated intervention aimed at supporting informal caregivers to cope with emotional distress via self-disclosing their emotions and needs to a social robot. Research has shown that informal caregivers often struggle in managing the emotional and practical demands of the caregiving situation, and also highlights the lack of social s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…The study's experimental design was replicated with a sample of informal caregivers (132; 133), who often experience high levels of emotional distress (134). The findings of the study replicated the previous results (131) and showed that caregiver participants felt less lonely and stressed, were more accepting of their caregiving situation, positively reappraised their caregiving situation and experienced reduced feelings of blame towards others (133).…”
Section: Anonymity and Rapport In Interactions With Social Robotssupporting
confidence: 55%
“…The study's experimental design was replicated with a sample of informal caregivers (132; 133), who often experience high levels of emotional distress (134). The findings of the study replicated the previous results (131) and showed that caregiver participants felt less lonely and stressed, were more accepting of their caregiving situation, positively reappraised their caregiving situation and experienced reduced feelings of blame towards others (133).…”
Section: Anonymity and Rapport In Interactions With Social Robotssupporting
confidence: 55%